2020
DOI: 10.2166/wst.2020.271
|View full text |Cite
|
Sign up to set email alerts
|

Start-up of a full-scale partial nitritation-anammox MBBR without inoculum at Klagshamn WWTP

Abstract: Partial nitritation and anaerobic ammonium oxidation (PNA) is a useful process for the treatment of nitrogen-rich centrate from the dewatering of anaerobically digested sludge. A one-stage PNA moving bed biofilm reactor (MBBR) was started up without inoculum at Klagshamn wastewater treatment plant, southern Sweden. The reactor was designed to treat up to 200 kgN d−1, and heated dilution water was used during start-up. The nitrogen removal was >80% after 111 days of operation, and the nitrogen removal ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…7 ). For the solely biofilm-based anammox process, AMX often resides in the inner layer of biofilms due to substrate diffusion that influences the electron competition among microorganisms (Dimitrova et al 2020 ; Li et al 2020 ; Pan et al 2019 ). But for double-sludge systems that segregate biomass between granules/biofilm and flocs, AMX normally flourishes in the outer layer of biofilms since the required can be readily provided by the nitrifiers in the flocculated sludge and the competition pressure from HB can also be shared by the flocculated sludge (Seuntjens et al 2020 ; Zhu et al 2018 ), which is the case of this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 ). For the solely biofilm-based anammox process, AMX often resides in the inner layer of biofilms due to substrate diffusion that influences the electron competition among microorganisms (Dimitrova et al 2020 ; Li et al 2020 ; Pan et al 2019 ). But for double-sludge systems that segregate biomass between granules/biofilm and flocs, AMX normally flourishes in the outer layer of biofilms since the required can be readily provided by the nitrifiers in the flocculated sludge and the competition pressure from HB can also be shared by the flocculated sludge (Seuntjens et al 2020 ; Zhu et al 2018 ), which is the case of this study.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of efforts have been devoted to the searching for suitable process configurations for mainstream anammox, and it is generally agreed that organic carbon–removal processes should be separated from anammox to avoid the competition between HB and AMX (Jia et al 2020 ). One reactor PNA has also been tested by using MBBR to offer a sanctuary for AMX, but the level of organic carbon in the influent should still be pre-reduced to limit the competition from HB (Dimitrova et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies for starting up and stable operation of anammox with BF at low nitrogen concentrations are limited. 13,14 Therefore, the study reported here was aimed at testing the feasibility of A-BF as an advanced nitrogen removal unit for tail water from the secondary treatment processes of MWWTPs with low nitrogen strength. Two A-BFs were started up under different TN concentrations (75 and 25 mg L −1 ) at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Proper control strategies are crucial for anammox BF (A‐BF) application in low nitrogen strength situations. However, studies for starting up and stable operation of anammox with BF at low nitrogen concentrations are limited 13,14 . Therefore, the study reported here was aimed at testing the feasibility of A‐BF as an advanced nitrogen removal unit for tail water from the secondary treatment processes of MWWTPs with low nitrogen strength.…”
Section: Introductionmentioning
confidence: 99%
“…To resolve these issues, we conducted continuous feeding tests and immobilized the cells in a polyethylene glycol (PEG) gel carrier (Isaka et al, 2007). Although several types of reactors for anammox processes have been reported, including the SBR, up-flow anaerobic sludge blanket (UASB), and moving-bed bioreactor (MBBR) (Strous et al, 1998;Strous et al, 1999;Sliekers et al, 2003;Furukawa et al, 2006;Dimitrova et al, 2020;Li et al, 2021;Peng et al, 2022). The gel entrapment technique was used to prevent the washout of anammox biomass from the reactor (Isaka et al, 2007).…”
Section: Introductionmentioning
confidence: 99%